2010
DOI: 10.3341/kjo.2010.24.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Lower Eyelid Epiblepharon Associated with Lower Eyelid Retraction

Abstract: PurposeTo describe a series of patients with lower eyelid epiblepharon associated with lower eyelid retraction.MethodsWe retrospectively reviewed the medical records of patients who underwent surgery for lower eyelid retraction, epiblepharon, or thyroid-associated ophthalmopathy (TAO) between October 1999 and March 2007. Patients with both lower eyelid retraction and epiblepharon on preoperative examination were included in this study.ResultsTwenty-seven eyelids of 20 patients with both lower eyelid retraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Increased intraorbital pressure in TED may lead to fat prolapse, predisposing to overriding of anterior lamella over the posterior lamella. 24 Lower lid retraction in TED may be involved in the pathogenesis of acquired epiblepharon, 29 as it was seen in 7 out of 8 patients with epiblepharon (87.5%). Lower lid retraction may occur secondary to fibrosis and shortening of the posterior lamella, and since the anterior lamella remains in its normal position, this results in anterior lamella overriding and the subsequent development of an acquired epiblepharon.…”
Section: Discussionmentioning
confidence: 94%
“…Increased intraorbital pressure in TED may lead to fat prolapse, predisposing to overriding of anterior lamella over the posterior lamella. 24 Lower lid retraction in TED may be involved in the pathogenesis of acquired epiblepharon, 29 as it was seen in 7 out of 8 patients with epiblepharon (87.5%). Lower lid retraction may occur secondary to fibrosis and shortening of the posterior lamella, and since the anterior lamella remains in its normal position, this results in anterior lamella overriding and the subsequent development of an acquired epiblepharon.…”
Section: Discussionmentioning
confidence: 94%
“…Fifty three TAO patients were diagnosed as an acquired lower eyelid epiblepharon, and 25 eyelids of 17 patients underwent surgical treatment; 7 eyelids of 4 patients from our previous report were also included [ 8 ]. Three patients were male and 14 patients were female with mean age of 38.3 years (SD, ±12.7 years).…”
Section: Resultsmentioning
confidence: 99%
“…Surgical management of TAO patients was generally performed in a serial order of orbital decompression, strabismus surgery, retraction repair, and eyelid surgery. As for an acquired lower eyelid epiblepharon in TAO patients, this principle should be also followed and epiblepharons were managed by orbital decompression first if there were accompanied exophthalmos or compressive optic neuropathy; it was reported that orbital decompression in TAO patients could also improve lower eyelid retraction and epiblepharon [ 8 ]. If epiblepharon does not resolve after orbital decompression and lower eyelid retraction was accompanied, then, retraction repair should be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition is usually not related to other eyelid abnormalities (Sung et al 2010). Sung et al (2010) described one rare occurrence of congenital epiblepharon associated with congenital eyelid retraction.…”
Section: Epiblepharonmentioning
confidence: 99%